Testamentary acts : - Millgate, Michael (Clarendon Press, 1992)
The testamentary acts of Michael Millgate's title are those strategies of self-protection and self-projection by which authors attempt in old age to enhance posterity's view of themselves and their work. The four figures examined in detail here–Robert Browning, Alfred Tennyson, Henry James, and Thomas Hardy–sought to maintain posthumous control over their personal privacy and the integrity of their finally approved texts by, for example, destroying documents, writing autobiographies, revising their earlier works and supplying them with retrospective prefaces, and publishing so-called 'collected' editions that in fact omitted items they no longer wished to preserve. Such strategies, though widely practised by writers, may yield altogether unanticipated results, and this study also examines the difficult role of such literary executors as Pen Browning, Hallam Tennyson, and Florence Hardy, called upon to exercise a delegated, hence compromised, authority. A concluding chapter gives briefer consideration to the wills and wishes of many other literary figures, from Samuel Johnson to Walt Whitman to Philip Larkin, and argues that biographers, editors, and readers in general need to be more attentive to these authorial end-games–to the often disregarded final years of writers and to the aims and consequences of their explicit and implicit testamentary acts.
Keywords: Biografie; Browning; Robert <1812-1889>; Hardy; Thomas <1840-1928>; James; Henry <1843-1916>; Tennyson; Alfred Tennyson <Baron; 1809-1892>; James; Henry; Hardy; Thomas; Browning; Robert; Tennyson; Alfred; Actes d'administration - Angleterre; Engels; Literaire nalatenschappen; Littérature anglaise - 19e siècle - Critique textuelle; Testaments; Écrivains anglais - Biographies - Histoire et critique; Englisch; Authors; English; Autobiography; Canon (Literature); English literature; Transmission of texts; Wills; Schriftsteller; Nachlass